Using estrogen and progesterone to treat premenstrual dysphoric disorder, postnatal depression and menopausal depression - Mu, Eveline; Chiu, Lauren; Kulkarni, Jayashri (Frontiers in Pharmacology, 2025)
Female gonadal hormones, particularly estrogen and progesterone, are not only central to reproductive health but also play a crucial role in regulating mood, cognition, and overall brain health. These hormones have a significant impact on the central nervous system, influencing key processes such as neurotransmission, neuroplasticity, and brain development. Increasing evidence shows that hormonal fluctuations contribute to the onset and progression of mental health disorders that disproportionately affect women, particularly premenstrual dysphoric disorder (PMDD), postnatal depression (PND), and menopausal depression. This paper explores the current evidence regarding the neurobiological effects of female hormones on the brain and discusses the therapeutic approaches in conditions such as PMDD, PND, and menopausal depression.